2014
DOI: 10.5761/atcs.oa.13-00241
|View full text |Cite
|
Sign up to set email alerts
|

Are Octogenarians in Good Condition after Cardiac Valvular Surgery?

Abstract: Kaplan-Meier analysis was used to assess survival. Hospital mortality was 1.6% (1 patient). The 3-, 5-, and 7-year survival rates were 81.2%, 75.4%, and 67.8%, respectively. The BI showed that 87.5% of patients did not require caregiving, the FIADL showed that 32.5% were highly independent, and the VI showed that 87.5% were motivated to live. Conclusions: Short-term outcomes were satisfactory, with low complication and mortality rates. Mid-term outcomes showed maintenance of the minimal required ADL and good m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…When some kind of assistance is needed, they receive 0 point. More than 4 points reflect high independence in IADL13 ) .…”
Section: Participants and Methodsmentioning
confidence: 99%
“…When some kind of assistance is needed, they receive 0 point. More than 4 points reflect high independence in IADL13 ) .…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Sumi, et al reported that in octogenarians with independent activities of daily living before surgery, cardiac valvular surgery was safe and postoperative quality of life was satisfactory. 26) It would be necessary for us to discuss the benefit of surgery for each patient in a heart team including cardiologists, cardiac surgeons, and other healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Various studies have reported worse outcomes in octogenarians; however, these reports have been primarily situated within the cardiac surgery literature. [6][7][8][9][10][11] Data on postoperative outcomes in octogenarians after vascular surgery, on the other hand, has been sparse and anecdotal.…”
Section: Introductionmentioning
confidence: 99%